Comparison of the Accuracies of CBCT, Radiography, and Four Electronic Apex Locators in Working Length Determination - Özata, Merve Yeniçeri; Falakaloğlu, Seda; Kaya, Sadullah (UI Scholars Hub, 2022)
Background: One of the significant stages during endodontic procedures is determining the correct working length (WL). This study aimed to evaluate the accuracy of four electronic apex locators (EALs) (Root ZX mini, Raypex 6, Propex Pixi, and E-Pex Pro) and cone-beam computed tomography (CBCT) and radiographic measurement in determining the actual WL (A-WL). Methods: Thirty extracted single-root mandibular premolars were selected and flattened at the crown. The WL was determined by advancing the #15 K file until its tip was visible from the apical, and the A-WL was established by subtracting 0.5 mm from this length. The WL was also determined using periapical radiography, four EALs, and CBCT. The differences in all measurements were compared with the A-WL. The data were statistically analyzed using one-way analysis of variance (Welch) and Tamhane’s test. The significance level was set at p < 0.05. Results: Compared with other measurement methods, CBCT gave shorter values than the A-WL, and this finding was statistically significant compared with those of the PR and Propex Pixi groups (p = 0.009) (p = 0.024). No significant difference was observed between the other groups (p > 0.05) except the CBCT group (p < 0.05). Conclusions: Root ZX mini and Raypex 6 made measurements close to the A-WL.